(untitled) (Revista Contexto & Saúde, 2022)
Objective: To analyze the Brazilian scientific production on quality of life (QOL), nutritional status (NS) and public policies of the elderly. Methodology: An integrative review of the literature was carried out, with evidence searches in the VHL, PubMed and Scielo databases in order to answer the question: Which factors most interfere in the quality of life of the elderly? Results: 15 articles were selected, being 9 on QOL, 5 nutritional status and 1 public policies of the elderly. There was a predominance of women, between 60 and 70 years of age, married, retired, receiving a minimum wage and with low schooling. Most perceived their QOL and Health as "Good." The most prevalent diseases were chronic noncommunicable diseases and most of the elderly practiced physical activity regularly. Regarding the nutritional status, excess weight and inadequate eating habits were the ones that stood out the most. Participating in activities in community centers promotes health and well-being and improves the perception of QOL. Conclusion: social determinants of health, physical activity, sex, age, economic class, nutritional and health status, and participation in a cohabitation group for the elderly are associated with the quality of life of the elderly. Keywords: Elderly. Nutritional status. Nutrition of the elderly. Health policy of the elderly. Quality of life.